2021
DOI: 10.1007/s00405-021-06945-9
|View full text |Cite
|
Sign up to set email alerts
|

Deep neck infections with and without mediastinal involvement: treatment and outcome in 218 patients

Abstract: Purpose Infections of the deep neck, although becoming scarcer due to the widespread use of antibiotics, still represent a dangerous and possibly deadly disease, especially when descending into the mediastinum. Due to the different specialities involved in the treatment and the heterogenous presentation of the disease, therapeutic standard is still controversial. This study analyzes treatment and outcome in these patients based on a large retrospective review and proposes a therapeutic algorithm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In fact, in our series, we found a male predominance of DNI patients, as widely recognized in many studies, even though the cause of such a prevalence remains largely unclear [9]. The mean age of our patients was 50.5 years, and this is consistent with the data presented in the literature [10].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, in our series, we found a male predominance of DNI patients, as widely recognized in many studies, even though the cause of such a prevalence remains largely unclear [9]. The mean age of our patients was 50.5 years, and this is consistent with the data presented in the literature [10].…”
Section: Discussionsupporting
confidence: 91%
“…Mediastinal collection is more often associated with oesophageal perforation or cardiothoracic surgery, but can develop in 3% of DNSIs 1 6. It is associated with neck pain, neck swelling, odynophagia, dysphagia, difficulty in breathing and tachycardia 1…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the technique used, in Lemierre’s syndrome source control is mandatory. In a recent analysis of 218 patients with deep neck infection with or without mediastinal involvement, the authors showed that immediate surgical drainage, broad empiric antibiotic therapy, surgical revision, antiseptic wound lavage, and early tracheostomy are the cornerstones of therapy [ 18 ]. Early tracheostomy is important to facilitate surgical revision and reduce sedation time and artificial ventilation duration [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%